Eksplorasi Motivasi Belajar Bahasa Arab Menggunakan Video pada Mahasiswa Magister Pendidikan Bahasa Arab - Makfiro, Nikmatul; Fithriyah, Aidah; Nidhomillah, Abd Rofi Fathoni; Mustofa, Syaiful (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Motivation plays a significant role in foreign language learning process, especially Arabic. A common issue among Arabic Language Education students is a lack of motivation. Among the causes of this lack of motivation are students' previous school backgrounds and the existence learning media which is capable of enhancing their motivation. Researchers attempt to provide a solution through learning videos on YouTube to boost the motivation of second-semester master's students in Arabic Language Education, Class C, at Maulana Malik Ibrahim State Islamic University of Malang. The chosen method for this research is qualitative descriptive with a narrative research design, aiming to describe data in a narrative writing style. Data collection technique employed in this research is interviews. According to the analysis of interview results with students, there are strong indications of increased learning motivation. The findings reveal that YouTube learning videos can significantly enhance students' motivation to learn Arabic. Based on students' accounts, the use of YouTube learning videos helps reinforce students' drive and learning needs, thus increasing their expectations and strong desire to achieve good learning outcomes. Learning Arabic via YouTube can be accessed anytime, creating a conducive learning environment. Additionally, learning through YouTube media is also perceived as engaging and interesting.